The image of successful specialist in technician and humanist students - Myshchyshyn, Maria (Lviv Polytechnic Publishing House, 2015)
The motivational role of image of successful specialist in the process of professionalization is presented. The peculiarities of successful specialist’s image in the minds of humanitarian and technician students are described with particular attention. The results of conducted study according to the professional qualities of successful specialist are presented. In the base of this study the model of successful specialist is elaborated. Joint for both groups are association of the successful specialist’s image with financial-software, high level of professional qualification and such components as professional conversation, competent, purposeful, forceful and honesty; difficult components are communication and empathy for humanitarian and responsibility with attentiveness for technician students.
Keywords: image; successful specialist; humanist; technician; professional and personal qualities